Penyuluhan kepada Masyarakat tentang Sediaan Farmasi Berbasis Bahan Alam di Sekolah Tanjung Pura Langkat - Natanael Priltius; Devina Chandra; Steven Tandiono; Manuppak Irianto Tampubolon (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Herbal plant-based pharmaceutical preparations are currently being developed because currently many industries produce and distribute pharmaceutical preparations containing natural ingredients that make it easier for the public to use. The purpose of this extension activity is to provide knowledge to the public about natural-based pharmaceutical preparations at schools in Tanjung Pura, Langkat. The method used in this activity involves lecturers by providing leaflets and materials to the public. The results of the implementation of this activity to the public are in the form of information and education about natural-based pharmaceutical preparations. The result of this activity is that the community service team hopes that the public will receive information about natural-based pharmaceutical preparations